Sharing Language: On the Problem of Meaning in Classic Buddhist and Brahmanical Traditions - Ben-Herut, Gil (Religions of South Asia, 2009)
This paper explores different philosophical approaches of Buddhists and Brahmanical thinkers during the first millennium, all of which revolve around the problem of assumed correlation between language and reality; i.e., the problems and ramifications that arise when we suppose that there is a correlation between language and reality. In this paper, I show that the indirect discussion between these thinkers greatly contributed to the developments of each distinct system of thought not only because of the explicit and obvious controversies between them but also because of the tacit agreements and latent counterinfluences that redefined and reshaped some aspects of theories of these thinkers. More concretely, I assert that Nāgārjuna’s use of language as a powerful tool to negate any ultimate existence of reality influenced considerably the completely opposite assertion made few centuries later by Bhartṛhari. In continuance to this notion, I assert that Bhartṛhari, in his turn, greatly contributed to the seminal epistemological explorations made by the Yogācāra School’s thinker Dharmakīrti. While these thinkers explicitly refute their opponent’s presuppositions and assertions, they simultaneously (and implicitly) also adopt some of their opponent’s argumentation and strategies to further develop their own assertions. To a certain extent, this paper is structured as a response to the work of Johannes Bronkhorst, who illustrated how some assertions that appear in Bhartṛhari’s seminal Vākyapadīya can be understood as directly influenced by Nāgārjuna’s assertions on the emptiness of language. Here, I hope to demonstrate, continuing the work of Bronkhorst, how Bhartṛhari, in his turn, might have influenced some thinkers of the Yogācāra School, chief among them Dharmakīrti. This paper serves as a positive echoing to the relatively minute scholarly effort to discuss similarities between philosophical rivals from classic India, as opposed to the general emphasis on doctrinal contestations.